2018
DOI: 10.3892/etm.2018.6070
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between coronary artery disease and obstructive sleep apnea syndrome and analysis of risk factors

Abstract: The correlation between coronary artery disease (CAD) and obstructive sleep apnea syndrome (OSAS) was investigated to analyze its risk factors. A total of 84 patients with suspected CAD due to chest tightness and pain or nocturnal angina, were selected. They were admitted and received coronary angiography in The Affiliated Hospital of Medical College Qingdao University from March, 2016 to June, 2017. The vital signs were monitored, and the sleep monitoring was performed before and after coronary angiography. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Therefore, raising the patient's awareness of the disease and its complications, and strengthening the early detection of OSAHS-related complications contribute to the treatment of disease and improvement of the prognosis of patients (15). The pathogenesis of OSAHS is upper airway obstruction (16), and OSAHS patients have neurohumoral abnormality (17). OSAHS can cause lesions in the cardiovascular system, and different types of CHD and OSAHS can also promote each other; thus, there is a complicated pathophysiological relation between OSAHS and CHD (18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, raising the patient's awareness of the disease and its complications, and strengthening the early detection of OSAHS-related complications contribute to the treatment of disease and improvement of the prognosis of patients (15). The pathogenesis of OSAHS is upper airway obstruction (16), and OSAHS patients have neurohumoral abnormality (17). OSAHS can cause lesions in the cardiovascular system, and different types of CHD and OSAHS can also promote each other; thus, there is a complicated pathophysiological relation between OSAHS and CHD (18).…”
Section: Discussionmentioning
confidence: 99%
“…Of practical relevance, it has recently been confirmed that OSAS is frequently associated with several vascular risk factors, and consequently with a greater risk of vascular events, and so it is likely that some of these patients will need statins [41,42,43]. In turn, there is evidence that Vit D deficiency is associated with a higher incidence of statin-related myopathy [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the higher the PSQI score as a continuous variable, the higher the risk of complex coronary lesions [35]. Zhang et al [36] investigated patients with OSA who had ACS, reporting that patients with severe OSA had a higher SYNTAX score than the mild group and the moderate group and that SYNTAX scores were positively correlated with AHI. In a prospective study, patients with OSA had significantly higher SYNTAX scores than those without OSA, and OSA was independently associated with CAD after adjustment for traditional risk factors [37].…”
Section: Discussionmentioning
confidence: 99%